Patrick Straram et l'utopie urbaine situationniste. - Vachon, Marc. (University of Ottawa (Canada), 2000)
This research offer a new perspective on the life and works of Patrick Straram in light of situationism. The association of Straram with the Quebec counter-cultural movement has overshadowed the profound influence of situationism on his life and works. Having participated to the foundation of the Internationale lettriste and introduce situationism in Quebec, he will pursue the situationist project throughout his existence. The situationist project correspond to a way of life base on the transformation of daily life and the urban environment in order to liberate the individual from the society of spectacle of modern capitalism. The situations urban vision differ from other architectural avant-garde due to it's cultural and artistic aspects inherited from the avant-garde movement of the 20th century (dadaism, futurism and surrealism). The cultural activities and the works of Straram are characterized by a critic of daily life, the integration of art and the transformation/appropriation of urban spaces necessary to the construction of situations. This research demonstrate that these various aspects correspond to the urban vision of the Internationale situationniste in regard to cultural and political actions. The analysis Straram's urban vision is base on the concept of unitary urbanism and its various components (detournement, derive, psychogeographie and construction of situations). Straram life and cultural productions constitutes a living critic of the rational city and represent a rare form of expression of the situationist urban utopia in North America. This thesis also demonstrate that many aspects of the urban and architectural theories of the Internationale situationniste continues to be incorporate in the contemporary urban and virtual environment.
Keywords: Geography.